Indonesian English: whats det tuh? - E. Aminudin Aziz (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
In a seminar on ESP held in Bandung, Andy Kirkpatrick of Curtin University of Technology, Australia, in relation to the anticipation of the potential emergence of a new variety of English in the Southeast Asian region and in Indonesia in particular, invited the audience, who were mostly university teachers, to start thinking about developing a teaching program based more on Indonesian culture than on, Anglo or American culture. This idea is based on the fact that Ã¢â¬Åthe vast majority of people in the region who are learning English are doing so with the expressed purpose of being able to use it as a lingua franca. They are not learning English to communicate with native speakers of English, but rather with other non-native speakersÃ¢â¬Â (Kirkpatrick 2001). While the idea is "stimulating and challenging" (Dardjowidjojo, 2001), cares need to be taken before we finally embark further to talk about it. This is particularly important because what we will need at the outset is the down-to-earth explorations discussing the issues related particularly with the unique features that will characterise the new variety of English (if at all any). In this paper, I explore some of the potential features and argue that the most prominent of all are the differences in the realisation in the acts of speech (and writing).